How Chemistry Shaped Societies: The Case of the Atacama Desert in Chile - Ureta-Zanartu, M (Springer Science and Business Media Deutschland GmbH, 2023)
Could the driest place in the world be a source of wealth for a country? This is the case for Chile and the Atacama Desert. The rise and fall of the saltpetre (NaNO3) industry is a very good example of how, in a short time (10 years), the development of a chemical technology reaches an exclusive fertilizer market and falls steeply when a new chemical technology (Haber–Bosch process) is developed, coupled with a global recession in 1930. This caused growth in Chile, a country that was growing rapidly, to stop abruptly, from the Great Depression until the middle of the twentieth century, when the copper mining boom began. However, the Atacama Desert continues to be a source of income for Chile, thanks to the extraction of copper and, recently, lithium. Solar plants are also a source of wealth. Graphical Abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.